PERBANDINGAN PENDAPATAN PETANI PALA (Myristica fragrans) BASAH DAN KERING DI DESA IE BUBOH, KECAMATAN MEUKEK - Tono Rahman (Nusantara Hasana Journal, 2023)
It is important to understand the comparative income of wet nutmeg farmers and dry nutmeg farmers, to identify the factors that affect farmers' incomes as well as initiate the advantages and challenges associated with each type of production. The purpose of this research was to find out the income ratio of wet nutmeg farmers and dry nutmeg farmers. The research was conducted in Ie Buboh Village, Meukek District, South Aceh Regency, from October to December 2021. The sample selection for the study was carried out deliberately, the number of samples was 30 respondents. The results showed that there were 3 types of dry nutmeg seed quality, which were seen based on water content (dry or not) and physical form (lucky or young fruit, moldy or not and the size of the fruit) where the quality quality was A, B and C. ., while at the pricing stage, it is determined by the buyer (trader). The income of wet nutmeg farmers is Rp. 1,350,000 and the income of dry nutmeg farmers is Rp. 3,410,130 with a ratio of 1:2.5. This shows that there is a significant comparison between the income of wet nutmeg farmers and dry nutmeg farmers in Ie Buboh Village, Meukek District.